Teacher preparation in Ireland : history, policy and future directions - O'Donoghue, T. A. 1953- (Emerald Studies in Teacher Preparation in National and Global Contexts, 2017)
This study of teacher preparation policy and practice in Ireland from Independence in 1921 to the present, highlights, within an international context, the extent to which the focus of preparation moved from nation-building until 1967, when free second-level education was introduced, to one concerned with improving the country's human capital.